Pembuatan Cetakan Pellet Elektroda Super Kapasitor Untuk Penyimpan Energi - yuli yetri; Eka Sunitra; Ali Siddik; Rakiman Rakiman; Haris Haris (Jurnal Teknik Mesin, 2023)
The design of a tool for printing supercapacitor electrodes has been completed. The basic material for the electrode is cocoa pod skin. The purpose of this research is to manufacture and assemble a laboratory-scale supercapacitor chip mold, which is used to facilitate the manufacture of the chip that functions as an electric current store. After the design process is complete, it is continued to manufacture supercapacitor chips using a press system. The actuator/pressurizer uses a hydraulic jack with a capacity of 50 tons, and a mold made of ST 37 and ST 60 steel. The mold is above the jack assisted by a steel frame as a pressure barrier. And a dial indicator as a marker to stop pressing by the jack. The process of making supercapacitor chip molds starts from cutting, drilling, turning, surface grinding, and welding. After the process of making components and assembling is complete, a trial of the tool is carried out to find out whether the tool works well. After a series of tests were carried out, it turned out that this pellet mold was able to print well without any cracks.